Epistemologi filsafat pengetahuan - Kenneth T. Gallagher (Kanisius, 1994)
ir,c.1/ oen, C.2/oen, c.3/sgh c.4/nd, c.5-7/tr, c.8/stoc2, c.1,4,6-8. 04sr1001135.03 (c.3) dalam pinjaman. c.2,c.5 tdk ditemukan.